Pressure‐induced structural phase transitions in bismuth tungstate Bi2WO6. Issue 4 (27th July 2021) - Lis, Olga N.; Kichanov, Sergey E.; Kozlenko, Denis P.; Belozerova, Nadezhda M.; Lukin, Evgeniy V.; Balakumar, Subramanian; Savenko, Boris N.
Abstract : The pressure‐induced structural polymorphism in bismuth tungstate Bi2 WO6 has been investigated by neutron diffraction and Raman spectroscopy. Abstract : The pressure‐induced structural phase transitions in bismuth tungstate Bi2 WO6 have been studied using neutron diffraction and Raman spectroscopy at high pressures up to 7 and 30 GPa, respectively. A rich structural polymorphism was revealed. At P ≃ 3.5 GPa a phase transition from the initial orthorhombic phase of P 21 ab symmetry to an orthorhombic phase of B 2 cb symmetry was observed. This transition is caused by the complex spatial rotation of the WO6 octahedra. A subsequent isostructural phase transition to another orthorhombic phase of B 2 cb symmetry was detected at P ≃ 5.9 GPa, accompanied by changes in both the mutual rotation and tilting of the oxygen octahedra with respect to the crystal b axis. Two more pressure‐induced phase transitions in Bi2 WO6 at high pressures of 11.5 and 20 GPa were observed in the Raman spectra. These pressure‐driven phase transitions in bismuth tungstate are accompanied by anomalies in the pressure dependences of the unit‐cell parameters, bond lengths and angles, and in the vibrational modes.